2020
DOI: 10.1002/1873-3468.13906
|View full text |Cite
|
Sign up to set email alerts
|

A novel function of Mycobacterium tuberculosis chaperonin paralog GroEL1 in copper homeostasis

Abstract: Among the two GroEL paralogs in Mycobacterium tuberculosis, GroEL1 and GroEL2, GroEL1 has a characteristic histidine-rich C terminus. Since histidine richness is likely to be involved in metal binding, we attempted to decipher the role of GroEL1 in chelating metals and the consequence on M. tuberculosis physiology. Isothermal titration calorimetry showed that GroEL1 binds copper and other metals. Mycobacterial viability assay, redox balance, and DNA protection assay concluded that GroEL1 protects from copper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The mycobacterial GroEL1 histidine-rich protein exists only as a monomer, even in the presence of stabilizers of oligomeric forms. , It has been discovered that Cu­(II) induces a response of the mycobacterial GroEL1 (M. tuberculosis) and its histidine-rich C-terminal region plays an essential role in this process . The histidine-rich motif is responsible for metal ion trafficking in a variety of organisms, including bacteria. It was predicted that proteins containing such specific sequences may be used as a molecular target for a new generation of medicines .…”
Section: Introductionmentioning
confidence: 99%
“…The mycobacterial GroEL1 histidine-rich protein exists only as a monomer, even in the presence of stabilizers of oligomeric forms. , It has been discovered that Cu­(II) induces a response of the mycobacterial GroEL1 (M. tuberculosis) and its histidine-rich C-terminal region plays an essential role in this process . The histidine-rich motif is responsible for metal ion trafficking in a variety of organisms, including bacteria. It was predicted that proteins containing such specific sequences may be used as a molecular target for a new generation of medicines .…”
Section: Introductionmentioning
confidence: 99%
“…GroEL1 contains a C-terminal histidine-rich region, which is a general feature of GroEL1 in actinobacteria. Recent studies showed that this region is involved in metal binding, which is required for GroEL1 function 66 , 67 , and it is possible that GroEL1 and PacL proteins evolved from a common ancestor to fulfill distinct functions.…”
Section: Discussionmentioning
confidence: 99%
“…GroEL1 contains a C-terminal histidine-rich region, which is a general feature of GroEL1 in actinobacteria. Recent studies showed that this region is involved in metal binding, which is required for GroEL1 function 65,66 , and it is possible that GroEL1 and PacL proteins evolved from a common ancestor to fulfil distinct functions.…”
Section: Discussionmentioning
confidence: 99%